Nurses should be trusted - like typists (press cutting)
1939-07-22 1937 1930s 2 pages D. Herald 22 JUL 1937 Nurses Should Be Trusted - Like Typists FROM OUR SPECIAL CORRESPONDENT BELFAST, Wednesday. BANISH THE NURSE'S TRADITIONAL UNIFORM, GIVE HER SHORTER HOURS, BETTER FOOD, AND THE SAME FREEDOM AS A BUSINESS GIRL. This was the emancipation plea put to the "Doctors' Parliament," which 1,500 medical members of the British Medical Association are attending here, by Dr. Peter W. Edwards, of Chester Sanatorium. Hours Bogey Speaking of the shortage of nurses, which, he thought, was not due to fears of infection, he said:— "Surely it is common sense that nurses do not volunteer, because of the conditions under which they have to work. "Their hours are too long. One inquiry has suggested reducing them to 51, another to 48. Cap Should Go "But why should nurses, who have to study and take examinations. have to work 48 hours a week? "The hours should be very much reduced, the nurses should be well fed and amply paid. They should not have to live in. "It is nonsense that a sister should have to ask the matron's leave to stay out after 10 o'clock at night. Women who can look after a ward of patients can look after themselves. "They should be treated like business girls. The traditional cap and apron should be banished from the wards — they should wear ward overalls." He also urged that tuberculosis among nurses should be regarded as an industrial disease, entitling them to compensation. 292/54.73/2/71